Laboratory Diagnosis of Mumps in a Partially Immunized Population: The Nova Scotia Experience. Issue 4 (2009) - Hatchette, TF; Davidson, R; Clay, S; Pettipas, J; LeBlanc, J; Sarwal, S; Smieja, M; Forward, KR
Abstract : BACKGROUND: In 2007, Atlantic Canada experienced a large outbreak of mumps predominately in university students who had received a single dose of measles, mumps and rubella vaccine. The present study describes the performance characteristics of reverse transcriptase polymerase chain reaction (RT-PCR) on buccal and urine specimens and immunoglobulin M (IgM) serology in this partially immune population. METHODS: Patients presenting with symptoms suspicious for mumps had a serum, urine and a buccal swab collected for diagnostic testing. Persons were classified as a 'confirmed' case according to the Public Health Agency of Canada's definition. Sera were tested using an enzyme-linked immunoassay. Detection of mumps virus in buccal swabs and urine samples was performed by RT-PCR. RESULTS: A subset of 155 cases and 376 non-cases that had all three specimens submitted was used for calculating the performance characteristics. The sensitivity of RT-PCR on buccal swabs, urine specimens and IgM serology were 79%, 43% and 25%, respectively. The specificity of RT-PCR on buccal swabs, urine specimens and IgM serology was 99.5%, 100% and 99.7%, respectively. Only 12 of 134 (9%) patients had positive urine specimens in the presence of negative oral swabs. CONCLUSION: RT-PCR on buccal swabs is the ideal specimen for diagnosis. Testing an additional urine sample in an outbreak setting did not increase the diagnostic yield significantly, but doubled testing volume and cost. In addition, the data suggest that, in this partially immune group, IgM serology has little value in the diagnosis of acute infection.